The Midnight zoo - Hartnett, Sonya (Candlewick Press, 2018)
Twelve-year-old Andrej, nine-year-old Tomas, and their baby sister Wilma flee their Romany encampment when it is attacked by Germans during World War II, and in an abandoned town they find a zoo where the animals tell their stories, helping the children understand what has become of their lives and what it means to be free.